On the particularities of postcolonial studies, or how postcolonialism has become obsolete - Sousa, Sandra (Programa de Pós-Graduação em Letras Vernáculas da Faculdade de Letras da UFRJ, 2017)
I draw first on Vivek Chibber's argument that postcolonial studies fails to provide an adequate basis for a theory of human rights and a practice of global solidarity. I then introduce the Warwick Research Collective's elaboration of a new theory of world literature constructed around the concept of “combined and uneven development.” I conclude by proposing a way out of the limitations of postcolonial studies.